Implementing the Result Decoding Algorithm of the Conditioned and Unconditioned Quest in Controling the Discipline Competence Level - Y. I. Kon; V. I. Freiman; A. A. Yuzhakov (Obrazovanie i Nauka, 2015)
The paper continues the authors’ previous publication (№ 6 (105), 2013) addressing the issue of quality assessment of educational outcomes in the Russian higher school. The research analyzes the approaches to creating and selecting the appropriate ways and means for the level assessment of the acquired disciplinary competences and their components – the disciplinary competence elements (DCEs); and demonstrates the structure of the conformity matrix of DCEs and corresponding educational outcomes. In addition, the algorithm of filling the matrix is illustrated along with the correlation of diagnostic indices and ratings with the assessment scales; the decoding algorithm of the unconditional testing procedure is described including the computation examples and outcome analysis. In conclusion, the authors consider the implementation options of the conditional testing procedure; analyze the related advantages, disadvantages, and proper conditions; and give recommendations for applying the given research materials.